2011
DOI: 10.1002/j.0022-0337.2011.75.4.tb05078.x
|View full text |Cite
|
Sign up to set email alerts
|

Underreporting of Bloodborne Exposures in a Dental School Clinic

Abstract: This study explored the rate of underreporting of bloodborne exposures among dental students in a U.S. dental school during the inal two years of clinical practice. It also explored the reasons students cite for failing to report bloodborne exposures. Surveys of the dental students found that senior students reported only 43 percent of the exposure incidents they experienced in their inal year of clinical education and that the rate of reporting declined from the junior year to the senior year. We subsequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
(13 reference statements)
1
9
0
Order By: Relevance
“…Of concern was the revelation that incidents were not reported despite the fact the instrument was contaminated. Our study findings also corroborate previous studies that show that exposures considered minor or perceived as low risk have a greater chance of not being reported, thus indicating participants’ lack of knowledge that all incidents should be reported. The extent of not reporting an exposure in this study is consistent with that of reported by Cuny et al .…”
Section: Discussionsupporting
confidence: 92%
“…Of concern was the revelation that incidents were not reported despite the fact the instrument was contaminated. Our study findings also corroborate previous studies that show that exposures considered minor or perceived as low risk have a greater chance of not being reported, thus indicating participants’ lack of knowledge that all incidents should be reported. The extent of not reporting an exposure in this study is consistent with that of reported by Cuny et al .…”
Section: Discussionsupporting
confidence: 92%
“…Exploring the number of BBP exposure incidents was not the sole objective of our study; nevertheless, findings seemed unexpectedly high, especially because research has shown that dental students generally underreport the number of BBP exposure incidents for reasons that can be explained by individual personality traits, gender, interpretation of the meaning of injuries, time away from patient treatment, low associated risk, and paperwork overload associated with reporting 27 , 28 . Furthermore, the rate of underreporting by dental students increases across the years of dental school as the fear of injury in the clinical context increasingly changes from being a function of individual factors to a function of knowledge acquired 27 , 28 . Students have self–reported a greater likelihood of injury later in their education than at the beginning, but a decreased fear of injuries as they gained clinical experience 29 …”
Section: Discussionmentioning
confidence: 83%
“…Our findings do not allow comparisons with the results of other studies that included information about other variables such as the number of patient visits and/or dental procedures performed 25 , 26 . Exploring the number of BBP exposure incidents was not the sole objective of our study; nevertheless, findings seemed unexpectedly high, especially because research has shown that dental students generally underreport the number of BBP exposure incidents for reasons that can be explained by individual personality traits, gender, interpretation of the meaning of injuries, time away from patient treatment, low associated risk, and paperwork overload associated with reporting 27 , 28 . Furthermore, the rate of underreporting by dental students increases across the years of dental school as the fear of injury in the clinical context increasingly changes from being a function of individual factors to a function of knowledge acquired 27 , 28 .…”
Section: Discussionmentioning
confidence: 84%
“…Available evidence strongly suggests that attitudes and behaviour vary across registrant groups and by experience (years in practice) for both exposure and reporting. 7,14,18,19,27 Considering different registrant groups and the length of time registrants have been in practice or qualified would be useful in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Evidence to date suggests that the greater proportion of sharps injuries occur as a result of inappropriate handling and disposal of instruments. 6,18,19 In addition, few studies have explored the attitudes and beliefs of primary dental care practitioners towards reporting occupational exposures in primary dental care. Given this combination of factors the aim of the study was to evaluate dentists' current reporting behaviour as well as their beliefs about reporting occupational exposures to blood and other oral fluids in Scottish dental practices.…”
Section: Aimsmentioning
confidence: 99%